Experimental and numerical investigation of the water-entry behavior of an inverted T-shaped beam - Xueyi Li; Feidong Zheng (Scientific Reports)
Abstract Objects entering water, characterized by brief and high-peak impact forces, have been extensively investigated in scientific research. However, the specific water entry process during docking downstream of the launching ship lift chamber involves T-shaped beams entering the water at a constant velocity with a deadrise angle of zero degrees. The hydrodynamic load mechanisms during this process remain not well understood. This research investigated the hydrodynamic loads generated as T-shaped beams from ship lift chambers enter water. Physical model experiments delineated the water entry process into three distinct phases: the entry impact phase, the cavity phase, and the braking phase. Furthermore, numerical simulations, validated by physical models, were employed to explore the factors influencing impact and cavity forces during the water entry process. These findings led to the derivation of empirical formulas to calculate the impact and cavity forces. These results support the assessment of structural forces on ship lift chambers, thereby enhancing the technical support and operational efficiency of ship lifts.